The Great Migration : Journey to the North - Greenfield, Eloise; Gilchrist, Jan Spivey (New York : Amistad, 2011)
Illuminates the experiences of families who left their homes in search of better lives during the move up north.
Includes bibliographical references.
003-008.
Keywords: African Americans -- Poetry; Children's poetry; American poetry